Estimating the impacts of climate change on fiscal health in the Philippines: Designing a policy toward a climate-resilient fiscal sector - John Paolo R. Rivera; Ramona Maria L. Miral; Mark Gerald C. Ruiz (Philippine Institute for Development Studies (PIDS), 2024)
We explored the fiscal impacts of climate-related phenomena in the Philippines and offer policy recommendations for creating a climate-resilient economy. By employing a threepronged empirical approach (i.e., time series, panel data, cross-section analyses), we probed on the nuanced interplay of climate shocks, fiscal health, and economic sustainability. Time series analysis highlighted how structural vulnerabilities, reliance on climate-sensitive sectors, and socio-economic inequalities exacerbate long-term scarring effects on growth. Panel data analysis emphasized temperature's acute impact on government consumption expenditure, contrasting with the mixed fiscal effects of rainfall and storms, shaped by mitigation measures and fiscal structures. Cross-section analysis elucidated further how local government units' fiscal resilience depends on external revenues, pre-allocated funds, and disaster severity. Findings revealed the need for region-specific fiscal responses, diverging from established scholarly literature due to the Philippines' decentralized disaster management and reliance on local institutions. Our policy recommendations include establishing a climate resilience fund, integrating climate-responsive budgeting, reinforcing risk transfer mechanisms, incentivizing green investments, and empowering local governments to manage adaptation funds. Additionally, investing in climate research, data-driven decision-making, and public awareness campaigns is critical. Aligning climate finance with long-term development plans and the 2030 Agenda for Sustainable Development ensures resilience is embedded within the broader development strategy. These steps aim to prepare the Philippines for climate-induced risks while fostering sustainable growth, mitigating fiscal shocks, and ensuring economic stability.
Keywords: 330; climate change; climate resiliency; fiscal balance; fiscal health; sustainability